Pengembangan Nilai-nilai Kewirausahaan dalam Meningkatkan Kinerja Usaha Rumput Laut Skala Kecil - Sahabuddin, Romansyah (Jurnal Trikonomika, 2012)
The purpose of this study was to obtain empirical evidence and find clarity of the development of personality values associated with achievement motivation, self efficacy and entrepreneurial commitment and its impact on business performance of seaweed small in province of South Sulawesi. The method used is survei research with data collection techniques using questionnaires to determine the small-scale seaweed entrepreneursâ assessment to the variables studied. The type of research is descriptive-verification. Sample size of 387 respondents drawn through proportional cluster random sampling technique from the targeted population of 11 370 small-scale seaweed entrepreneurs spread over ten districts of South Sulawesi province. To test the hypothesis proposed, structural equation modeling (SEM) is used as a model framework that is composed through the measurement model and structural model of causal relationships among variables. The implication of this study is that the entrepreneurial commitment has contributed a more dominant influence of achievement motivation and self efficacy on the business performance, either directly or indirectly through an entrepreneurial commitment.